A new species of Petasiger (Digenea, Echinostomatidae) parasitizing Podiceps major and Rollandia rolland (Aves, Podicipedidae) from Buenos Aires Province, Argentina - Lunaschi de Redolatti, Lía Inés (2010)
Petasiger argentinensis sp. nov. is described from material found in the intestine of the Great Grebe, Podiceps major (Boddaert) and the White-tufted Grebe, Rollandia rolland Quoy et Gaimard (Podicipediformes, Podicipedidae), from Argentina. The new species is characterized by the head collar armed with 19 spines and by the testes arranged in tandem. These characters are shared with only two Neotropical species of the genus, P. novemdecim Lutz, 1928 and P. combesi Zamparo, Overstreet et Brooks, 2005. Petasiger novemdecim differs from the new species in having a larger body, longer collar spines, larger eggs, a cirrus-sac of similar size to the ventral sucker and almost entirely anterior to it, and vitelline fields confluent ventrally posterior to the ventral sucker. P. combesi differs from the new species in most metrical characters, the shape of the body (antero-posteriorly elongate) and the location of the genital pore (dextral) and the excretory pore (dorsal). This is the first record of a member of the genus Petasiger parasitizing birds from Argentina.